Olympic and Paralympic athletes` perceptions of the Canadian sport environment and mental health - Poucher, Z. A.; Tamminen, K. A.; Kerr, G. (Qualitative Research in Sport, Exercise and Health, 2023)
While athletes can experience poor mental health, researchers often focuses on the personal factors that impact an athlete`s mental health. Such a narrow focus neglects the broader contextual factors, such as involvement within sport systems, that can impact athlete mental health. Purpose: The purpose of this project was to understand how elite sport training environments in Canada impact the mental health of athletes. Methods: Team Canada Olympic and Paralympic athletes (n = 32) from team and individual sports (water polo, basketball, rowing, athletics, swimming, gymnastics, and field hockey) each participated in one semi-structured interview. Data were analysed using thematic analysis. Results: Athletes identified environmental features that supported and detracted from their mental health, including: the provision of resources, social support, performance pressure, communication, language, and coaching. These features impacted athletes` mental health experiences by influencing their perceptions of stigma, their perceptions of mental health as an organisational priority, their help-seeking behaviours, and the minimisation of their personal experiences. Discussion: Uncertainty and a lack of control were common features of the environment contributing to athletes` perceptions of stress and negatively impacted their wellbeing, as did a lack of trust in support providers and negative coaching practices. While some environmental features impacted athletes` mental health directly, many had an indirect impact on athletes` mental health (e.g. led to the minimisation of personal mental health challenges). Identifying ways to enhance athlete autonomy and educate coaches about mental health and supportive coaching practices are important directions for future research and practice.